A mind to murder [videorecording (DVD)] - James, P. D.; Marsden, Roy, 1941-; Finlay, Frank, 1926-2016; Flynn, Jerome, 1963-; Davies, Gareth; James, P. D. (P.D. James the essential collection, 2008)
"Investigating a savage death at an exclusive psychiatric clinic, Dalgliesh is caught in a whirlwind of political intrigue and deceit"--Koch Entertainment booklet.